A revision of the gudgeon genus Hypseleotris (Gobiiformes: Gobioidei: Eleotridae) of northwest Australia, describing three new species and synonymizing the genus Kimberleyeleotris - Shelley, James J.; Delaval, Aurélien; Feuvre, Matthew C. Le (Zootaxa, 2023)
Species within the northwest Australian clade of Hypseleotris (six species) and the genus Kimberleyeleotris (two species) are reviewed following the recording of new populations in the region and a molecular study of the group that identified three undescribed candidate species. Based on the analysis of extensive morphological and nuclear and mitochondrial molecular datasets, Kimberleyeleotris is here formally synonymised with Hypseleotris. Furthermore, three species from the Kimberley region, Western Australia, are described to science: Hypseleotris maranda sp. nov., Hypseleotris wunduwala sp. nov., and Hypseleotris garawudjirri sp. nov. The presence of, or number of scales across the head and body, the pattern of sensory papillae on the head, fin ray counts, dorsal and anal fin colouration (particularly in breeding males), and body depth, can be used to distinguish the members of the northwest Australia lineage. Furthermore, the newly described species were genetically separated from all northwest Australian congeners by K2P distances ranging from 7.8–11.3% based on the CO1 gene, and 7.7–16.3 % based on the entire mitochondrial genome. Two of the new species, H. maranda sp. nov. and H. wunduwala sp. nov., have extremely narrow ranges being found in single sub-catchments of the Roe and King Edward Rivers respectively. On the other hand, H. garawudjirri sp. nov. is moderately widespread, being found across the Charnley, Calder, and Sale rivers. While the conservation risk to H. maranda sp. nov. and H. wunduwala sp. nov. is inherently high due to their small range, there are currently no obvious local threatening processes to either of these species given their remote locations that are little impacted by human activities.